The effect of different levels of supplementary feed on the production of finisher ostriches (Struthio camelus) grazing irrigated lucerne (Medicago sativa) pastures - Strydom, Marline (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2010.